Intrauterine Growth Restriction Induces Adulthood Chronic Metabolic Disorder in Cardiac and Skeletal Muscles - Li, Ping; He, Lewei; Lan, Yue; Fang, Jie; Fan, Zhenxin; Li, Yifei (Frontiers in Nutrition, 2022)
Objective Although population-based studies of intrauterine growth restriction (IUGR) demonstrated a series of postnatal complications, several studies identified that IUGR could definitely cause dysfunction of metabolism of cardiac and skeletal muscles in the perinatal period and early life. However, it is still unknown if such metabolic alternation would remain for long term or not, and whether normal protein diet administration postnatally would protect the IUGR offsprings from a “catch-up growth” and be able to reverse the premature metabolic remodeling. Materials and Methods We established an IUGR rat model with pregnant rats and a low-protein diet, and the developmental phenotypes had been carefully recorded. The cardiac and skeletal muscles had been collected to undergo RNA-seq. Results According to a series of comparisons of transcriptomes among various developmental processes, programmed metabolic dysfunction and chronic inflammation activity had been identified by transcriptome sequencing in IUGR offsprings, even such rats presented a normal developmental curve or body weight after normal postnatal diet feeding. Conclusion The data revealed that IUGR had a significant adverse impact on long-term cardiovascular function in rats, even they exhibit good nutritional status. So that, the fetal stage adverse events would encode the lifelong disease risk, which could hide in young age. This study remaindered that the research on long-term molecular changes is important, and only nutrition improvement would not totally reverse the damage of IUGR.